EXAMINING CODE-SWITCHING PRACTICES IN HILMAN HARIWIJAYA'S MAKHLUK MANIS DALAM BIS AND BUNGA UNTUK POPPI (TWO NOVELS TAKEN FROM THE SERIES OF LUPUS) - Martiana, Tia (2012)
This study, entitled Examining Code-switching Practices in Hilman Hariwijaya's Makhluk Manis Dalam Bis and Bunga Untuk Poppi (Two Novels Taken from the Series of Lupus), aims to investigate types and functions of code-switching in the characters' conversations in two novels written by Hilman Hariwijaya. The discussion is framed within Poplack's theory (1980) related to types of code-switching and functions of code-switching theory proposed by Koziol (2000 as cited in Fauzia, 2008; Ramdhani, 2010; and Hendriyani, 2012).The data are analyzed by implementing qualitative method through several stages, i.e. underlining the code-switching in the characters' conversations; classifying the code-switching into their types and functions; and quantifying the frequency each type and function. Afterwards, the data are interpreted and discussed to draw the conclusions of the study.The results of data analysis show that there are three types of code-switching, namely intra-sentential switching (95.06%), inter-sentential switching (2.64%), and tag-switching (2.3%). Considering the frequency of code-switching, Intra-sentential switching (95.06%) is the most frequent type of code-switching found, whereas tag-switching (2.3%) is the least frequent type. Regarding the functions, there are 13 functions of code-switching: emphasis (49.20%), designation (10.92%), clarification (9.12%), objectification (6.15%), aggravating message (5.73%), parenthesis (5.73%), mitigating message (3.71%), topic shift (3.28%), untranslatability (3.28%), personalisation (1.06%), interjection (0.85%), reiteration (0.64%), and quotation (0.32%). Emphasis (49.20%) is the most dominant function of code-switching while quotation (0.32%) is the least frequent function. Moreover, the results indicate that the author of the novels posseses good ability of English and Bahasa Betawi. Keywords: Lupus, Code-switching, Types and Functions of Code-switching.